2021
DOI: 10.1134/s251775162106010x
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Membranes without Proteins but with Aqueous Nanochannels and Facilitated Transport. Minireview

Abstract: Imitation of biological membranes and aqueous channels attracts more and more attention. In this review, we mention both the early and very recent papers in this area. Still, we concentrate our attention on less known biomimetic membranes, which are commercial nitrocellulose ultrafilters, impregnated by esters of fatty acids. Pores in filters are filled with lipid-like oils, but aqueous nanochannels are spontaneously formed on the inner pore surfaces with carboxylic groups fixed on nitrocellulose. This combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…The accumulation of saturated long-chain FFAs in liver mitochondria incubated with divalent cations was confirmed previously [ 38 , 46 ], and their participation in Ca 2+ /H + and K + /H + exchange in the organelles was proposed [ 48 ]. Recent data also suggest that fatty acids in the presence of calcium ions can induce self-sustaining fluctuations in transmembrane voltage and current in biomimetic membranes without proteins [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of saturated long-chain FFAs in liver mitochondria incubated with divalent cations was confirmed previously [ 38 , 46 ], and their participation in Ca 2+ /H + and K + /H + exchange in the organelles was proposed [ 48 ]. Recent data also suggest that fatty acids in the presence of calcium ions can induce self-sustaining fluctuations in transmembrane voltage and current in biomimetic membranes without proteins [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different biomimetic membranes [ 1 , 2 , 3 ] can be used for ex situ prebiological drug screening and to predict their penetration and interactions with biological membranes [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The membranes are ~ times thicker than biological membranes, but their many specific (after recalculation to the same thickness) fundamental physicochemical properties are similar to those of biomembranes. Therefore, our membranes may be called biomimetic membranes and are discussed in more detail in a recent review [ 3 ], where many references to original papers may be found.…”
Section: Introductionmentioning
confidence: 99%